The implementation of e-learning in the educational process - Bozhok, Natalia (My University, 2015)
The Internet has fundamentally changed the practice of teaching and learning during the last ten years, especially in colleges and universities that are well equipped with new technology. Інтернет докорінно змінили практику викладання та навчання протягом останніх десяти років, особливо в коледжах і університетах, які добре оснащені новою технологією.
Keywords: e-learning; educational process; implementation; електронне навчання; реалізація; навчальний процес; электронное обучение; учебный процесс; реализация; кафедра ділової іноземної мови та міжнародної комунікації